Changes in Socio-Demographic Factors of Bangladesh: Links with Poverty - Md. Idris Ali; Md. Faisal-E- Alam (CV. Literasi Indonesia, 2022)
The primary purpose of this study is to investigate how poverty is changed along with four socio-demographic factors. The study is descriptive, using panel data from 2007 to 2019 by employing Trend Line and Correlation of Coefficient. The Trend Line depicts that life expectancy is increasing, literacy is rising, the population growth rate is fixed, the infant mortality rate is a downtrend, and poverty has been reduced over thirteen years in Bangladesh. The Correlation results showed that the correlation between life expectancy rate and poverty rate as well as literacy rate and poverty rate are negative but significant statistically. Besides, the population growth rate and poverty rate, as well as the infant mortality rate and poverty rate, are correlated and statistically significant. The outcomes indicate that an increasing pattern of life expectancy rates and literacy will decrease the poverty rate in Bangladesh. In addition, the population growth rate and high infant mortality rate increase the poverty rate in Bangladesh. The government should formulate a time-oriented fair policy so that rapid growth of the economy, foreign investment, and capacity to manage risks connected with natural calamities and investment in farming and infrastructure is possible to alleviate poverty. Finally, it is suggested that multidimensionality such as regional disparity and mental health conditions should measure empirically to know the causes of poverty in Bangladesh.